Desintegración familiar y su incidencia en la ansiedad de un niño de 8 años del cantón Vinces - Guerrero Maldonado, Jocelyne Odalys (2022)
The family for the infant is a means of vital protection in its development, in the same way when this is a risk the infant is greatly harmed predisposing the appearance of some mental pathology, such as anxiety disorders, therefore, it was raised as The objective in this case study is to determine how family disintegration affects the anxiety of an 8-year-old boy from the Vinces canton, for this psychological techniques and instruments were used to collect information, which were medical history, psychometric battery , which was constituted by the Bender Visual-motor test to evaluate brain damage and emotional indicators of the child, the Corman family test and the STAIC anxiety test, in addition to an observation sheet, thanks to the results obtained it is possible to establish as presumptive diagnosis F93.80 Generalized anxiety disorder in childhood, therefore the need to work therapeutically was seen Uses the findings of parental neglect, obsessive ideas, episodes of anxiety, feelings of guilt, low academic performance, through the cognitive behavioral approach with the cognitive behavioral approach, with psychoeducation techniques, cognitive restructuring, guided discovery, extreme distraction and responsibility analysis. , concluding that the stated objective was achieved since it is determined that family disintegration causes erroneous behaviors around the relationship with the patient, generating this stress beyond its resistance capacity, causing the appearance of generalized anxiety disorder in childhood.